The Auricular Cartilage in 197 Secondary and Tertiary Rhinoplasties. Issue 2 (March 2016) - Pascali, Michele; Gentile, Pietro; Di Pasquali, Camilla; Bocchini, Ilaria; Cervelli, Valerio
Abstract : Background: The purpose of this study was to describe and evaluate the efficacy of the use of auricular cartilage to treat aesthetic and functional deformities of patients who underwent secondary rhinoplasty o tertiary. Methods: From July 2005 to July 2014, 197 patients (144 women and 53 men) underwent rhinoplasty with the use of cartilage grafts. A total of 137 patients (70%) underwent secondary rhinoplasty, 60 patients (30%) underwent tertiary rhinoplasty. Patients in whom the Cottle maneuver was positive (108 patients, 55%) underwent a rhinomanometry test and responded to a simple questionnaire that reported on their nasal patency. Patients were evaluated at 6, 12, 24 months after surgery. Results: The results of this study revealed an effective correction of aesthetic deformities of patients and a significant improvement in airway patency in 108 patients with respiratory obstruction. No major complication was observed. Conclusions: The use of auricular cartilage graft is efficacy to solve aesthetic and functional remnants after an incorrect procedure, or primary or secondary.